Aproveitamento dos rejeitos da agroindústria de leite no município de Nossa Senhora da Glória/Semi-árido de Sergipe : caracterização e perspectivas de desenvolvimento sustentável - Costa, Antônio Wilson Macedo de Carvalho (2005)
The industrialization of the milk in the Sergipe semi-arid presents, nowadays, several kinds of cheese as main product, despising as slips many components with high nutritious value, provoking, beyond the economical loss, an environmental aggression. This study presents two integrations focus: (1) the technological question, with the characterization of the milk agriculture-industry slips, with the purpose of identifying economical and technological possibilities of utilization of the components of rejected nutritious value; and (2) the environmental question of these slips utilization, with the purpose of decreasing the environmental impacts and then guaranteeing the region development. Considering the context of the Nossa Senhora da Glória county, characterized as farming subsistence, the possibility of adapting the industrialization process with the social-economicalenvironmental questions will allow a more including social scope, promoting the improvement of the region life quality, as long as the milk industrialization process presents, in the technological question, considerable losses and environment impacts proportional, needing urgently of consolidated development alternatives in the principles of sustentation. The slips characterization, in this study, is made by means of physicchemistry and microbiological assays. The economical losses are calculated in function of the load and average productions of the agriculture-industries, considering their slips production, with the purpose of characterizing the agriculture-industries inside the context and suggesting alternatives of development, reducing the environmental impacts and allowing the sustainable development of the Sergipe semi-arid.